(untitled) (Research, Society and Development, 2022)
Bone deformities, whether congenital or resulting from trauma, present a challenge for their repair because it is a lengthy process with often unpredictable results, with high economic importance. Tissue engineering consists of the regeneration of living organs and tissues, through the development of new devices capable of obtaining specific interactions with biological tissues, known as scaffolds. The PLA (poly lactic acid) polymer is promising for use as a temporary support for tissue replacement because it is biodegradable, biocompatible and has low cost. However, its hydrophobic characteristic is one of the main disadvantages of using this polymer. Therefore, current research aims to modify the surface of these devices in order to make them more hydrophilic. This study aimed to evaluate the surface modification of PLA scaffolds, chemically treated with sodium hydroxide (NaOH) to evaluate cell adhesion and viability in scaffolds on alkaline treatment with NaOH. The FTIR-ATR (Attenuated Total Reflectance Fourier Transform Infrared) and AFM (Atomic Force Microscopy) techniques were used for physical-chemical characterization of the material, adhesion and cell viability assay by the fluorimetric method with the resazurin reagent. The AFM and FTIR analyzes confirmed the surface modification of the material by the alkaline treatment. By analyzing cell adhesion, it was concluded that the treatment did not influence adhesion, but was more effective in maintaining cell viability.